2014
DOI: 10.1016/j.ijdevneu.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal caffeine intake differently affects synaptic proteins during fetal brain development

Abstract: Caffeine is the psychostimulant most consumed worldwide. However, little is known about its effects during fetal brain development. In this study, adult female Wistar rats received caffeine in drinking water (0.1, 0.3 and 1.0 g/L) during the active cycle in weekdays, two weeks before mating and throughout pregnancy. Cerebral cortex and hippocampus from embryonic stages 18 or 20 (E18 or E20, respectively) were collected for immunodetection of the following synaptic proteins: brain-derived neurotrophic factor (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…Well before birth, hippocampal and cortical neurons in the brain express BDNF and TrkB (Behar et al, 1997; Mioranzza et al, 2014). Exogenous BDNF increases the number of primary dendrites in an activity dependent manner through TrkB in specific cortical layers (McAllister et al, 1997; McAllister et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Well before birth, hippocampal and cortical neurons in the brain express BDNF and TrkB (Behar et al, 1997; Mioranzza et al, 2014). Exogenous BDNF increases the number of primary dendrites in an activity dependent manner through TrkB in specific cortical layers (McAllister et al, 1997; McAllister et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, exposure of immature brain cells to CAF or SADs reduces mRNA and protein levels of BDNF [6,2426], and altered BDNF expression by CAF or SADs has been implicated in neuroapoptosis [27] and long-term neurodevelopmental impairment [25,28]. In addition, CAF [29] and SADs [27,28] have been shown to downregulate activity of the pro-survival Akt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly also, caffeine actions do not result solely from A 2A R antagonism since caffeine is an antagonist of different adenosine receptor subtypes. However, several studies have indeed shown that gestational exposure to caffeine may alter the normal development of the brain with cognitive consequences to the adult brain (Juárez-Méndez et al 2006;Soellner et al 2009;Silva et al 2013;Mioranzza et al 2014), by delaying migration and insertion of GABAergic neurons into the hippocampal circuitry (Silva et al 2013), by decreasing either BDNF or TrkB receptor levels (Mioranzza et al 2014), by affecting the different adenosine receptors expression during neural Fig. 11 Adenosine A 2A Rs activation increases microtubule dynamics.…”
Section: Adenosine a 2a Receptor Activation Increases Microtubule Dynmentioning
confidence: 99%